Sporadic adenoma in ulcerative colitis: endoscopic resection is an adequate treatment. Issue 8 (19th January 2006) - Vieth, M; Behrens, H; Stolte, M
Abstract : Background and aims: In studies with small numbers of cases, it has been shown that endoscopic resection of adenomas in ulcerative colitis represents adequate treatment. In a larger study cohort with more prolonged follow up, we assessed the reliability of this finding. Methods: Between 1988 and 2002, 148 consecutive patients, mainly from private gastroenterologists' practices, with ulcerative colitis were diagnosed as having an adenoma. In 60 patients, histological diagnosis was established in biopsies and in 87 patients in polypectomy specimens; one patient underwent proctocolectomy following diagnosis. The outcome of these patients was analysed after a mean follow up period of 6.0 (3.63) years. Results: Among 60 patients, surprisingly without endoscopic treatment, 48.3% developed ulcerative colitis associated neoplasia in the same colon segment (23.3% low grade intraepithelial neoplasia; 8.3% high grade intraepithelial neoplasia; 16.7% carcinoma). Among 87 patients undergoing polypectomy of the adenoma, follow up revealed colitis associated neoplasia in other segments of colon in 4.6% of cases. Conclusion: Development of adenocarcinomas in a total of 6.7% of the overall patient group, and in 2.3% of those undergoing polypectomy, indicates that biopsy based diagnosis of an adenoma in ulcerative colitis must be considered to mandate endoscopic resection of the lesion; 40% of affected patients did not receive any form of endoscopic removal of the lesion. This shows that the most recent guidelines are not followed in a considerable number of patients with ulcerative colitis in private practice in Germany. Although polypectomy of the adenoma represents adequate therapy, further regular follow up examinations are nevertheless necessary.